Ecophysiological Leaf Traits of Forty-Seven Woody Species under Long-Term Acclimation in a Botanical Garden - Qinglin Sun; Liming Lai; Jihua Zhou; Xin Liu; Yuanrun Zheng (Plants, 2022)
Ex situ conservation plays an important role in the conservation and utilization of plant resources. In recent years, botanical gardens have greatly improved the ex situ conservation of plants, and research has mainly focused on morphological characteristics, reproduction technology, and conservation value. There are few studies on the ecophysiological traits of plants after conservation. Forty-seven plants that are frequently used in North China and were grown in the Beijing Botanic Garden were selected to measure their photosynthetic traits, light-use efficiency (LUE), water–use efficiency (WUE), specific leaf area (SLA), relative chlorophyll content (SPAD), and leaf water potential (φ). An analysis of variance showed that there were significant differences in the ecophysiological traits of the leaves of 47 woody species. The light saturation point (LSP), net photosynthetic rate at light saturation (Pnmax), φ, and SLA had significant differences among different plant life forms. The SLA and SPAD of leaves were significantly different among the families. The LUE of all species reached its maximum under a low light intensity, and species with a large difference between the light saturation point and light compensation point had larger Pnmax values. This research further adds to the understanding of the adaptation mechanisms of plants to the environment under the conditions of a botanical garden as well as the environmental fitness in a long-term ex situ domestication and then helps with scientifically setting up artificial management conditions.